2017
DOI: 10.1177/0269216317690479
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of family care-givers at end of life: A national post-bereavement census survey of cancer carers’ hours of care and expenditures

Abstract: Background:Family members provide vital care at end of life, enabling patients to remain at home. Such informal care contributes significantly to the economy while supporting patients’ preferences and government policy. However, the value of care-givers’ contributions is often underestimated or overlooked in evaluations. Without information on the activities and expenditures involved in informal care-giving, it is impossible to provide an accurate assessment of carers’ contribution to end-of-life care.Aim:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 31 publications
1
107
0
1
Order By: Relevance
“…Five studies reported caregivers' OOPCs, which most frequently included the cost of care supplies, medication, formal help (e.g. professional care or paid domestic help) and travel expenses, although each study included different OOPCs (Table ; Guerriere et al, ; Hanly, Céilleachair, Skally, O'Leary, Kapur, et al, ; Lauzier et al, ; Rowland, Hanratty, Pilling, van den Berg, & Grande, ; Van Houtven et al, ). Two studies found that OOPCs make up 7%–13% of total caregiver costs in studies that included OOPCs, care time and work time costs, depending on the phase of disease (Hanly, Céilleachair, Skally, O'Leary, Kapur, et al, ; Van Houtven et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies reported caregivers' OOPCs, which most frequently included the cost of care supplies, medication, formal help (e.g. professional care or paid domestic help) and travel expenses, although each study included different OOPCs (Table ; Guerriere et al, ; Hanly, Céilleachair, Skally, O'Leary, Kapur, et al, ; Lauzier et al, ; Rowland, Hanratty, Pilling, van den Berg, & Grande, ; Van Houtven et al, ). Two studies found that OOPCs make up 7%–13% of total caregiver costs in studies that included OOPCs, care time and work time costs, depending on the phase of disease (Hanly, Céilleachair, Skally, O'Leary, Kapur, et al, ; Van Houtven et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The OOPCs most often reported by caregivers were related to travel expenses, household costs (e.g. bills) and medication or care supplies (Guerriere et al, ; Hanly, Céilleachair, Skally, O'Leary, Kapur, et al, ; Rowland, Hanratty, Pilling, Berg, & Grande, ). Four studies provided detailed information regarding the value of individual OOPCs, which showed that in general, travel costs and formal care costs were the most expensive OOPCs, although this varied across studies (Guerriere et al, ; Hanly, Céilleachair, Skally, O'Leary, Kapur, et al, ; Rowland et al, ; Van Houtven et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This model incorporates a supportive role into mainstream palliative care, rather than a model where the support role is independent to palliative care and perhaps is one that could be considered a compromise in how people at the end of life are supported. With costs of care already high for individuals and families at the end of life (Rowland, Hanratty, Pilling, van den Berg, & Grande, ), a death doula, unless in a voluntary role, is thereby only a viable option for those who can afford them.…”
Section: Discussionmentioning
confidence: 99%
“…An under-examined issue in economics of palliative care is the family caregiver perspective, addressed by articles from Rowland et al, 5 Dzingina et al 6 and Brick et al 7 While studies have looked in some detail at system costs, and in particular recorded a consistent pattern of cost-savings with respect to hospital costs, we know that hospital inpatients represent a minority of people with palliative care need and that formal utilisation of services does not fully reflect the cost of caring for someone with serious illness. Thus, the dataset compiled by Rowland and colleagues indicating that in England caregivers spend an average of 10 h/day, as well as substantial amounts of their own money, in end-of-life cancer care gives food for thought on how health systems and societies can provide care in an equitable and fair manner.…”
Section: Current State Of the Economics Of Palliative And End-of-lifementioning
confidence: 99%